Organizational Resources and Performance of Kenyan State Corporations - Ongeti, Walter, J.; Machuki, Vincent, N. (European Scientific Journal, ESJ, 2018)
Organizational resources have been posited to influence organizational performance. However, this position has been largely tautological with need for more empirical grounding. The postulations of resource based theory confer a significant effect of resources on organizational performance only when they possess some strategic characteristics. In spite of this postulation, comparative management advances an argument that management is sensitive to the context in which it is practiced; hence empirical testing of the postulation is inconclusive. This study tested the influence of organizational resources on the performance of Kenyan state corporations. Through a crosssectional descriptive survey, data on resources and performance were obtained from 63 Kenyan state corporations and analyzed using both descriptive and inferential statistics. The findings report a statistically significant relationship between aggregated organizational resources and performance. However, organizational resources could only explain 8.3 percent of performance of Kenyan state corporations. Results of the independent effect of disaggregated organizational resources indicated statistically significant effect of tangible, human and intangible resources on performance. Statistically not significant results were reported for the effect of organizational capabilities on performance. The findings provide partial empirical support for the Resource Based Theory by supporting the postulations that resources possessed by an organization influence performance by establishing the independent contributions of each resource to performance. It has offered direction for dayto- day managerial practice as well as policy direction at both organizational and government levels. At managerial level, practitioners may consider strengthening resource integration, renewal as well as recombination for stellar performance. Government policy should be focused towards encouraging resource acquisition, integration, configuration, and combination that would have a stronger influence on performance. From the limitations of the study, areas for further research have been pointed out.